2018
DOI: 10.1074/mcp.ra118.000877
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Contribution of Proteasomal Spliced Peptides to the HLA-I Ligandome*

Abstract: It has been reported that about 30% of the HLA-I ligands are produced by proteasomal splicing of two noncontiguous fragments of a parental protein. We report that the identification of many of those spliced peptides is ambiguous. With an alternative workflow, based on de novo sequencing and subsequent verification with multiple search tools, we estimate that the upper bound for the proportion of cis-spliced peptides is 2–6%. Nevertheless, the true contribution of spliced peptides to the ligandome may be much s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
96
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 35 publications
12
96
0
Order By: Relevance
“…For 9 of our previously published HLA class I-expressing monoallelic datasets , our current data analysis found 308 nuORF-derived peptides, supported by Ribo-seq, that map to the same MS/MS spectra as 343 proposed spliced peptides , in either of two scenarios: (1) for 98 cases, the nuORF-derived peptide sequence is identical to a proposed spliced peptide (Supplementary Figure 6a,b); or (2) for 210 cases, the partial sequence present in the MS/MS spectrum matched to a nuORF-derived peptide is also consistent with one or more different, yet similar, spliced peptide sequences ( Supplementary Figure 6c,d). Notably, while 84% of nuORF peptides and 94% of annotated peptides had predicted MHC I binding scores over 0.8 (Methods), only 33% of proposed spliced peptides did (Figure 2i), consistent with reports that many spliced peptides were incorrectly identified (Rolfs et al 2019;Mylonas et al 2018). This suggests that stringent FDR thresholds and careful attention to sequence ambiguities resulting from de novo MS/MS interpretations are particularly warranted when interpreting the MS/MS spectra of peptides derived from noncanonical sources.…”
Section: Short Overlapping Nuorfs Identified In the Mhc I Immunopeptsupporting
confidence: 82%
See 2 more Smart Citations
“…For 9 of our previously published HLA class I-expressing monoallelic datasets , our current data analysis found 308 nuORF-derived peptides, supported by Ribo-seq, that map to the same MS/MS spectra as 343 proposed spliced peptides , in either of two scenarios: (1) for 98 cases, the nuORF-derived peptide sequence is identical to a proposed spliced peptide (Supplementary Figure 6a,b); or (2) for 210 cases, the partial sequence present in the MS/MS spectrum matched to a nuORF-derived peptide is also consistent with one or more different, yet similar, spliced peptide sequences ( Supplementary Figure 6c,d). Notably, while 84% of nuORF peptides and 94% of annotated peptides had predicted MHC I binding scores over 0.8 (Methods), only 33% of proposed spliced peptides did (Figure 2i), consistent with reports that many spliced peptides were incorrectly identified (Rolfs et al 2019;Mylonas et al 2018). This suggests that stringent FDR thresholds and careful attention to sequence ambiguities resulting from de novo MS/MS interpretations are particularly warranted when interpreting the MS/MS spectra of peptides derived from noncanonical sources.…”
Section: Short Overlapping Nuorfs Identified In the Mhc I Immunopeptsupporting
confidence: 82%
“…First, nuORF and annotated MS/MS-detected peptides had similar Spectrum Mill MS/MS identification scores (11.7 nuORF vs. 11.4 annotated mean scores, 95% CI: 0.27-0.43), median peptide length (9AA), and translation levels (1.7 nuORF vs. 1.6 annotated mean log2TPM, 95% CI: 0.09-0.19) (Figure 2a-c, Supplementary Figure 3b-d). Second, chromatographic retention times for nuORF peptides correlated as well with predicted hydrophobicity indices as they did for annotated peptides (p=0.55, rank-sum test) (Figure 2d, Supplementary Figure 3e) (Mylonas et al 2018;Rolfs et al 2019). Finally, two-dimensional projection of pairwise distances amongst detected peptide sequences per allele showed that anchor residue motifs of nuORF-derived peptides matched closely to peptides derived from annotated proteins (Figure 2e, Supplementary Figure 3f,g) with a strong agreement in peptide sequences across all alleles (Pearson r 2 = 0.85 nuORFs, r 2 = 0.92 annotated) (Figure 2f).…”
Section: Nuorf Derived Peptides Are Presented On Mhc Isupporting
confidence: 54%
See 1 more Smart Citation
“…Mylonas et al . performed de‐novo sequencing of MS/MS spectra to identify the sequences of peptides eluted from MHC class I molecules isolated from various human tissues and cell lines (melanoma tissues, B cell lines and fibroblast cells) . Sequences identified de novo were matched to genomically‐encoded protein sequences in databases.…”
Section: Discovery Of Hips Utilizing Mass Spectrometrymentioning
confidence: 99%
“…These ambiguous findings, highlight the necessity of a widely accepted methodology for spliced peptide identification. 55 Nevertheless, the relevance of spliced peptides in antigen presentation is also highlighted by their high affinity to MHC class I molecules and by their ability to activate CTL responses as extensively as linear antigenic peptides. 50,56,57…”
Section: Degradation and Regulatory Mechanismsmentioning
confidence: 99%